Facile and sustainable shear mixing/carbonization approach for upcycling of carton into superhydrophobic coating for efficient oil-water separation. (20th September 2018) - Yuan, Shi-Jie; Zhang, Jia-Jia; Fan, Hao-Xiang; Dai, Xiao-Hu
Abstract: The development of facile and sustainable methods to produce efficient oil-water separation materials is an important and challenging problem. This paper presents a simple and green shear mixing/carbonization approach for the upcycling of old corrugated containers into a superhydrophobic coating (OCF-600), which can be applied to a suitable sponge material and used to clean up oil spills and organic solution leaks. There is a synergetic effect between the shear mixing and carbonization processes. The water contact angle of OCF-600 (152.57 ± 1.50°), which is obtained by the shear mixing/carbonization process using cartons as the only precursor, is significantly larger than that of materials obtained by individual shear mixing or carbonization methods, and even larger than that of carbon material obtained by carbonization/shear mixing process (138.85 ± 0.85°). The shear mixing drastically enhanced the surface roughness, whereas the carbonization led to the formation of the hydrophobic groups, further strengthened its micro-roughness, and amplified the surface property to superhydrophobicity. The OCF-600 can easily be coated onto several substrates to form superhydrophobic materials for efficient oil-water separation with excellent durability and selectivity, even under corrosive and turbulent conditions. The OCF-600 coated sponges exhibited favorable adsorption capacities range from 18 to 44 times their own weight for various kinds of oils and organic solvents. The OCF-600 coated microporous membrane can separate surfactant-stabilized oil-water emulsions with a separation efficiency of greater than 99.88%. Furthermore, this approach can be extended to a series of cellulosic waste, thus could open up new prospects for the fabrication of superhydrophobic coatings through the sustainable upcycling of waste products. Graphical abstract: Image 1 Highlights: A facile method of upcycling old corrugated container into superhydrophobic coating. It is obtained by 5 min shear mixing in a kitchen blender before the carbonization. There is a synergetic effect between the shear mixing and carbonization processes. It excellent durability and selectivity offers great promise to application. This shear mixing approach can be extended to a series of cellulosic waste.